Effects of Cytotoxic T Lymphocytes (CTL) Directed against a Single Simian Immunodeficiency Virus (SIV) Gag CTL Epitope on the Course of SIVmac239 Infection - Allen, Todd M. (American Society for Microbiology, 2002)
Vaccine-induced cytotoxic T lymphocytes (CTL) have been implicated in the control of virus replication in simian immunodeficiency virus (SIV)-challenged and simian-human immunodeficiency virus-challenged macaques. Therefore, we wanted to test the impact that vaccine-induced CTL responses against an immunodominant Gag epitope might have in the absence of other immune responses. By themselves, these strong CTL responses failed to control SIVmac239 replication.